Cooperation Businesses in the Świętokrzyskie Voivodeship – Opportunity or Barrier to the Devolopment of Regional Innovation System? - Nowak, Paulina (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The innovation of the regions economy is the making of development of regions. An important element of the economic competitiveness of regions is also the cooperation of businesses between them and with scientific circles. The development of cooperative networks depends mainly on the will of companies and their mutual trust. The creating and developing cooperation links of świętokrzyskie firms should not be the strongest in the country. Świętokrzyskie companies have, so far, limited and inconsistent business partnerships. This situation presents an important barrier to the development of the regional innovation system.